2019
DOI: 10.1021/jacs.8b13884
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Oxygen-Embedded Quinoidal Pentacene and Nonacene

Abstract: Extension of oxygen-embedded polycyclic aromatic hydrocarbons (PAHs), in particular with a defined topology, is synthetically challenging primarily because of limited regio-specific methods and poor solubility of PAHs. We reported herein an efficient way to construct quinoidal pentacenes and nonacenes with regular zigzag O-inserted edges. These O-embedded backbones composed of benzene, pyranyl, and cyclohexa-1,4-diene moieties provided access to a new class of longitudinally conjugated acenes with superior sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…[10] This time scale is much shorter than the time scale for injection of PA Hs synthesized in carbon-rich outflows of AGBs tars of some 10 9 years. [10] Therefore,t he presence of PA H-like material in the interstellar medium suggests that ac ritical synthetic pathway to PA Hs at low temperatures is missing.T he mechanisms elucidated here might fill the gap and can provide aunique route to PA Hs at temperatures as low as 10 K. These mechanisms are of interest in organic chemistry and can be linked to material sciences as they provide insight into reactivity,bond-breaking processes,a nd synthesis of extended p-conjugated systems involving acyclic precursors (vinylacetylene) with extensive applications as building blocks for molecular wires, [16] carbon nanotubes [17] and graphene [18] along with molecular organic semiconductors for organic field effect transistors [19] and organic light emitting diodes. [20] Briefly,ahigh-temperature chemical reactor was utilized to investigate the reaction of distinct anthracenyl and phenanthrenyl radicals ([C 14 H 9 ]C)w ith vinylacetylene (C 4 H 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] This time scale is much shorter than the time scale for injection of PA Hs synthesized in carbon-rich outflows of AGBs tars of some 10 9 years. [10] Therefore,t he presence of PA H-like material in the interstellar medium suggests that ac ritical synthetic pathway to PA Hs at low temperatures is missing.T he mechanisms elucidated here might fill the gap and can provide aunique route to PA Hs at temperatures as low as 10 K. These mechanisms are of interest in organic chemistry and can be linked to material sciences as they provide insight into reactivity,bond-breaking processes,a nd synthesis of extended p-conjugated systems involving acyclic precursors (vinylacetylene) with extensive applications as building blocks for molecular wires, [16] carbon nanotubes [17] and graphene [18] along with molecular organic semiconductors for organic field effect transistors [19] and organic light emitting diodes. [20] Briefly,ahigh-temperature chemical reactor was utilized to investigate the reaction of distinct anthracenyl and phenanthrenyl radicals ([C 14 H 9 ]C)w ith vinylacetylene (C 4 H 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of PAH‐like material in the interstellar medium suggests that a critical synthetic pathway to PAHs at low temperatures is missing. The mechanisms elucidated here might fill the gap and can provide a unique route to PAHs at temperatures as low as 10 K. These mechanisms are of interest in organic chemistry and can be linked to material sciences as they provide insight into reactivity, bond‐breaking processes, and synthesis of extended π‐conjugated systems involving acyclic precursors (vinylacetylene) with extensive applications as building blocks for molecular wires, carbon nanotubes and graphene along with molecular organic semiconductors for organic field effect transistors and organic light emitting diodes true[C14H9]4pt+4ptnormalC4normalH44pt4pt[C18H13]4pt4ptnormalC18normalH124pt+4ptnormalH …”
Section: Introductionmentioning
confidence: 99%
“…We revealed that this unusual reactivity originates from the intense intramolecular energy in the highly strained structure. Besides, recently, O-doping of polycyclic aromatic hydrocarbons (PAHs) is emerging as a powerful strategy to tailor the optoelectronic properties of π-conjugated molecular modules 42. This study presents a new concept for the preparation of potential sensing agents and O-doped PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned observations about the presence of the colorful species are most likely attributed to the O-doped PAHs with different sizes of π-conjugated systems formed as a result of NOG nanosheets decomposition. In fact, tailoring of the PAHs' electronic structure with the purpose of acquiring novel optical properties comprising color and PL by means of bottom-up synthesis of oxygen-embedded π-conjugated systems has been well documented [49][50][51] . In this respect, a study focused on the O-annulation of PAHs for the synthesis of different compounds with diverse band gaps, colors and PL emissions has great conformity with the observations regarding the NOG fibers 52 .…”
Section: Sample C/o C % (C=c) % (C-c/c-h) % (C-o) % (C=o) % (O-mentioning
confidence: 99%